Exploring the Effect of Yiqi Huatan Huoxue Recipe on Inflammatory Injury in Autoimmune Thyroiditis (AIT) Mice via Pyroptosis/Apoptosis Pathways Based on the SIRT1/NF-κB/NLRP3 Signaling Axis - Zhao, Zhuo; Liu, Ziyu; Song, Nan; Cao, Huimin; Chen, Yiran; Chen, Si; Wang, Zhimin; Jin, Zhe; Yang, Xiao (Combinatorial Chemistry & High Throughput Screening, 2025)
ObjectiveAutoimmune thyroiditis (AIT) is the most common autoimmune thyroid disease. In recent decades, its incidence and prevalence have sharply increased. Yiqi Huatan Huoxue recipe is a traditional Chinese medicine formula we use to treat AIT. Its clinical efficacy is clear, but the specific mechanism remains unclear. This study aims to explore whether pyroptosis mediated by the SIRT1/NF-κB/NLRP3 Pyroptosis signaling pathway is one of the therapeutic mechanisms of Yiqi Huatan Huoxue recipe.MethodsForty 8-week-old female NOD.H-2h4 mice were randomly divided into four groups: the normal group (NG), model group (MG), Yiqi Huatan Huoxue recipe group (YG), and western medicine group (selenium yeast tablet, SeG). The normal group was gavaged with distilled water, while the remaining groups were gavaged with 0.05% sodium iodide (NaI) solution for 8 weeks. After the AIT animal model formed naturally, the mice were euthanized by gavage after 8 weeks. Hematoxylin-eosin staining was used to observe thyroid tissue changes, and enzyme-linked immunosorbent assay (ELISA) was used to detect serum anti-thyroglobulin antibodies (TGAb) and mouse anti-thyroid peroxidase antibodies (TPOAb). Real-time quantitative PCR (qRT-PCR), Western blot, and immunohistochemistry were used to detect the expression of sirtuin 1 (SIRT1), nuclear factor κB p65 (NF-κB p65), nod-like receptor protein 3 (NLRP3), Absent in melanoma 2(AIM2)、 apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), Cysteinyl Aspartate-Specific Protease-1(caspase-1), gasdermin D (GSDMD), interleukin (IL)-1β 、BCL2- Associated X(Bax)、B-cell lymphoma-2(Bcl2)and Caspase-3 in thyroid tissue.ResultsCompared with NG group, the thyroid structure of MG group rats was severely damaged, lymphocyte penetration was obvious, serum TGAb and TPOAb levels were significantly increased, the expression levels of NF-kB p65, NLRP3, AIM2, ASC, Caspase-1, GSDMD, IL-1β, Bax, Caspase-3 mRNA and protein were significantly increased, and the expression levels of SIRT1 and Bcl2 mRNA and protein were significantly decreased. Compared with the MG group, the thyroid structural damage and lymphocyte invasion of rats in each treatment group were improved. The serum mRNA and protein expression levels of TGAb, TPOAb, NF-kB p65, NLRP3, AIM2, ASC, Caspase-1, GSDMD, IL-1β, Bax, Caspase-3 were significantly reduced, and the expression levels of SIRT1 and Bcl2 mRNA and protein were significantly increasedConclusionYiqi Huatan Huoxue recipe can reduce thyroid structural damage and apoptosis in AIT mice. The mechanism may be related to the up-regulation of SIRT1 and NF kB deethylation, and the inhibition of NLRP3 and AIM2-mediated pyroptosis.
Keywords: apoptosis